DEFORESTATION ISSUE CONSTRUCTION FROM THE TAKNALAWE’ EPIC OFDAYAKKAYAAN WEST KALIMANTAN - Budi, Budi; Herdiani, Een; Heriyawati, Yanti (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2023)
Takna' Lawe' is an oral tradition of the Kayaan people. Lii' Long and Ding Ngo wrote down this oral tradition in a book entitled Poetry Lawe'. The epic Takna' Lawe' is famous for the story of heroism and love from the figure of Lawe'. Apart from this story, there are also signs from the Takna' Lawe epic which constructs the issue of deforestation. This study is focused on the interpretation of the signs in the episode "Hingaan Stuck in Beraan". This episode is found in the book Poetry Lawe', which was rewritten in prose in Indonesian. The purpose of this research is to reveal the meaning behind the story in the hope that people will become aware of the dangers of deforestation that are currently happening in Kalimantan. This study uses qualitative methods with Paul Ricoeur's hermeneutical approach. The analysis is carried out through the stages of semantic meaning, phenomenological meaning, and ontological meaning to produce a new contextual meaning. The results of the research show that there is a meaning that leads to the issue of deforestation, namely exploitation and destruction of forests, the anger of nature, and disasters for natural destroyers, including actions against ancestral teachings.